2022
DOI: 10.1093/toxres/tfac027
|View full text |Cite
|
Sign up to set email alerts
|

Drp1-mediated mitochondrial fission promotes carbon tetrachloride-induced hepatic fibrogenesis in mice

Abstract: Background Mitochondrial dynamics is essential for the maintenance of healthy mitochondrial network. Emerging evidence suggests that mitochondrial dysfunction is closely linked to the pathogenesis of hepatic fibrogenesis following chronic liver injury. However, the role of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission in the context of liver fibrosis remains unclear. Methods and Results In this study, C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We found that the voltage-dependent anion channel lying in the mitochondrial outer membrane contributes to radiation-induced mtDNA release, which can be blocked by the VDAC1 inhibitor DIDS. Mitochondrion is an important organelle of eukaryotic cells, and also acts as a target for various environmental factors [ 37 , 38 , 39 , 40 , 41 ]. Some damage stresses, such as H 2 O 2 , high glucose, LPS, and IR, were reported to increase mtDNA release into the cytosol [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the voltage-dependent anion channel lying in the mitochondrial outer membrane contributes to radiation-induced mtDNA release, which can be blocked by the VDAC1 inhibitor DIDS. Mitochondrion is an important organelle of eukaryotic cells, and also acts as a target for various environmental factors [ 37 , 38 , 39 , 40 , 41 ]. Some damage stresses, such as H 2 O 2 , high glucose, LPS, and IR, were reported to increase mtDNA release into the cytosol [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A key factor in the mitochondrial fission process is the activity of dynamin-related protein 1 (DRP1), which acts strictly on apoptosis by mediating the process of fission [ 112 ]. It was suggested that the loss of liver DRP1 may enhance the inflammatory response [ 112 ], and its phosphorylation, as a consequence of ROS products, encourages the fission process [ 113 ]. Moreover, findings from 2022 highlighted that excessive mitochondrial fission may make a certain contribution to the progression of NAFLD, while the inhibition of this process was correlated to a decrease in hepatic injuries and endoplasmic reticulum (ER) stress [ 106 ].…”
Section: Oxidative Stress and Inflammation In Non-alcoholic Fatty Liv...mentioning
confidence: 99%
“…For example, excessive DRP1-triggered mitochondrial fission takes part in apoptosis in various pathological conditions, and thus it has emerged as a promising therapeutic target. A recent study revealed that DRP1-mediated mitochondrial fission promotes carbon tetrachloride-induced liver fibrosis and may function as a therapeutic target for retarding the progression of chronic liver disease ( Shan et al, 2022 ). Mitochondrial division inhibitor 1 (Mdivi-1) has been revealed to play a valuable role in various diseases by inhibiting DRP1-mediated mitochondrial fission ( Deng et al, 2021 ; Ding et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%